Pengaruh Interval Waktu Pemupukan Dan Konsentrasi Pupuk Organik Cair (POC) Terhadap Pertumbuhan Dan Hasil Bayam Merah (Amaranthus tricolor L) - Untung Yahudi; Windu Mangiring; Yatmin Yatmin; Krisnarini Krisnarini; Fizzaria Khasbullah (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2022)
Liquid organic fertilizer is fertilizer that is applied to the leaves. The advantage of fertilizer application through leaves is that nutrients are more easily absorbed by plants, both macro and micro nutrients. This study aims to determine the time intervals of fertilization and differences in the concentration of liquid organic fertilizer on the growth and yield of red spinach, as well as to determine the interaction between the two. The treatment used was the time of fertilization and the difference in the concentration of liquid organic fertilizer. The results showed that the timing of fertilization had a significant effect on the weight of red spinach plants. The time interval of fertilization every 3 days gave better results, namely 18.94 g. And there is no interaction between time interval and concentration of liquid organic fertilizer on the growth and yield of red spinach for all variables.